2021
DOI: 10.1101/2021.07.02.21258881
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Break-through COVID-19 infection rate with Indian strain in Single-center Healthcare Workers – A real world data

Abstract: Introduction: It is observed that many healthcare workers got COVID19 infection despite of completing both doses of Covishield vaccine. This study aimed to find real incidence of vaccine breakthrough infection. Material and methods: All hospital employees, who were fully vaccinated were included in study. Details about their vaccine side effects, infection prior to vaccination, post vaccination infection, severity of infection, hospital and ICU admission were noted. Results: None encountered any significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
4
6
0
Order By: Relevance
“…Comparison with other studies is mentioned in Table 4. The mean age of patients with breakthrough infections was 35.07 (±10.38) years and most of the vaccinated individuals, as well as the, vaccinated infected individuals were females i.e, 79.83% and 75% respectively similar to the findings of Sabnis R et.al [17].…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Comparison with other studies is mentioned in Table 4. The mean age of patients with breakthrough infections was 35.07 (±10.38) years and most of the vaccinated individuals, as well as the, vaccinated infected individuals were females i.e, 79.83% and 75% respectively similar to the findings of Sabnis R et.al [17].…”
Section: Resultssupporting
confidence: 84%
“…The breakthrough infection rate among the vaccinated health care workers in the previous studies was found to be 18.65% and 13.3% [14,15] and it is 6.58 % in our study. Comparison with other studies is mentioned in Table 4.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…We finalized 18 studies from across the world[ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 ] that fully filled all the inclusion criteria, with 2,30,000 healthcare workers as shown in the flow chart. All studies were of high quality based on the “New-Castle Ottawa Scoring System.” The ratio of the vaccinated and the non-vaccinated individuals was 16.4:1, whereas the ratio of the fully vaccinated to partially vaccinated individuals was 1.12:1.…”
Section: R Esultsmentioning
confidence: 99%
“…[ 5 6 7 8 9 10 ] The data available vary among different populations with reinfections. [ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 ] Hence, we conducted a systematic review and meta-analysis of infections breakthrough after COVID vaccination among healthcare workers.…”
Section: Introductionmentioning
confidence: 99%